Peran Palang Merah Indonesia Dalam Penanggulangan Bencana Alam - Imelda I; Nafisah Nadia; Ummu Nabila Marpaung; Usiono U (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the role of the Indonesian Red Cross (PMI) in disaster management. The research used is a qualitative descriptive study, employing literature review as the method. Data sources were gathered from previous studies such as journals, scientific articles, books, and other relevant materials that support the topic. The results of this research indicate that the role of PMI volunteers in non-disaster situations can be divided into two phases: mitigation and potential disaster response. In the mitigation phase, volunteers are involved in training, outreach, information dissemination, raising awareness, and conducting disaster simulations. When there is a potential disaster, they monitor threats, provide emergency response training, and prepare basic needs and recovery equipment. During an actual disaster, volunteers conduct search and rescue, evacuation, provide field kitchens, temporary shelters, protection for vulnerable groups, and assist in emergency recovery, information dissemination, and psychosocial support for victims.